2017
DOI: 10.1097/id.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Sinus Membrane Elevation by the Crestal Approach Using a Novel Drilling System

Abstract: Sinus membrane elevation by the crestal approach using special reamers is advantageous because of the noticeable reduction in the risk of perforation and the ability to perform the surgery rapidly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 14 publications
2
17
0
1
Order By: Relevance
“…The positive results attributed to this kit demonstrated in this study are in concordance with the results observed in the ex vivo study of Yassin Alsabbagh et al, , where the SCA drill kit was shown to be superior to the osteotome technique in osteotomy preparation and breaking the sinus floor. These results were later corroborated in a clinical study by Kim et al, , who did not report any membrane perforations using the SCA drill kit, but reported an incident of acute maxillary sinusitis 5 months after surgery. This may have been related to a possible undetected perforation during the elevation surgery.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The positive results attributed to this kit demonstrated in this study are in concordance with the results observed in the ex vivo study of Yassin Alsabbagh et al, , where the SCA drill kit was shown to be superior to the osteotome technique in osteotomy preparation and breaking the sinus floor. These results were later corroborated in a clinical study by Kim et al, , who did not report any membrane perforations using the SCA drill kit, but reported an incident of acute maxillary sinusitis 5 months after surgery. This may have been related to a possible undetected perforation during the elevation surgery.…”
Section: Discussionsupporting
confidence: 59%
“…If this occurs, a number of consequences may entail: the presence of bone graft within the sinus antrum, acute or chronic sinus infection, the invasion of bacteria into the site or disrupted maxillary sinus physiologic function (Katranji et al, ; Li & Wang, ). With all the proposed methods of crestal SFE (Chan et al, ; Kim et al, ; Yassin Alsabbagh et al, ), MT (Wen, Lin, Yang, & Wang, ) RRH (Schwarz et al, ), the amount of bone graft inserted and VEH (Sonoda, Harada, Yamamichi, Monje, & Wang, ) are factors that influence the probability of membrane perforation. In this study sample, MT was not statistically significant between the two study groups, enabling a fair comparison of all other factors between test and control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, other improved TSFE has been proposed; these include but are not limited to the balloon technique (Chan et al, ; Yassin Alsabbagh et al, ), the hydraulic elevation technique (Bensaha, ; Better et al, ; Tallarico, Better, De Riu, & Meloni, ), the piezotome technique and the reamer system (Yassin Alsabbagh et al, ). Among the TSFE techniques proposed, the reamer system (e.g., SCA‐Neobiotech, Seoul, South Korea) exhibits less trauma compared with other TSFE techniques (Gargallo‐Albiol, Tattan, Sinjab, Chan, & Wang, ; Kim, Lee, Park, Kim, & Oh, ; Yassin Alsabbagh et al, ).…”
Section: Introductionmentioning
confidence: 99%